Program Evaluation and Approval Rating: Evidence from Indonesia’s Free Nutritious Meals and Red and White Cooperative Programs - Widiyatmoko, Faris; Agustianto , Hasyim Nawawi (Universitas Brawijaya, 2026)
This study analyzes the relationship between public opinion on the government’s priority programs and the approval ratings of President Prabowo Subianto and Vice President Gibran Rakabuming Raka. The study focuses on the Free Nutritious Meals (MBG) and the Red and White Cooperative (KMP) programs. This study employs a quantitative approach using a survey method. The findings show that program evaluation is more strongly associated with approval rating than program awareness. Although awareness of MBG and KMP exhibits significant relationships in some models, these effects are relatively weak and inconsistent. In contrast, satisfaction with MBG and confidence in the future success of KMP are consistently and positively associated with approval ratings of both political leaders. The findings further indicate that both retrospective and prospective evaluations contribute to approval ratings.